Effect of a Stress-Management Intervention Based on Self-efficacy Theory for Enriching Marital Relationships and Sleep Quality in Primigravida Women - Zeinab Alizadeh; Farzaneh Noroozi; Mohammad Hossein Kaveh; Rosanna Cousins; Leila Ghahremani (Journal of Health Sciences and Surveillance System)
Background: A woman’s first pregnancy is a significant life event, and anxieties related to pregnancy and childbirth arecommon during this time. This study aimed to evaluate the effect of a stress-management intervention based on self efficacy in primigravida women, as indicated by improvements in sleep quality, relationship quality, and marital satisfaction.Methods: A quasi-experimental design with a control group was used. Inclusion criteria included being at 14–18 weeks ofgestation, having no concomitant illness, and attending one of four healthcare centers in South Iran in 2022. Two centers were randomly allocated to the intervention group and the other two to the control group. Of the 128 eligible pregnant women consented to participate, 39 were randomly assigned to each condition. The intervention group completed eight weekly one-hour stress-management training sessions using a blended learning approach. Data were collected using a survey administered before and immediately after the intervention. The survey included demographic information and validated questionnaires measuring self-efficacy, marital satisfaction, relationship quality, and sleep quality. Data were analyzed using independent and paired t-tests to evaluate the efficacy of the intervention by comparing changes in mean scores between the two groups pre-and post-intervention.Results: There were no confounding differences between participants in the two groups at the pre-test. Self-efficacy, sleep quality, marital satisfaction, and relationship quality were significantly improved in the post-test in the intervention group (P<0.01). No meaningful changes were observed in the control group.Conclusion: T he r esults s uggest t hat i ntegrating s tressmanagement workshops into routine prenatal care may be beneficial. Providing facilities and support for such interventions could enhance maternal well-being during pregnancy.